Kemampuan Pemecahan Masalah Matematis pada Penyelesaian Soal Jumping Task Berdasarkan Adversity Quotient Peserta Didik - Prasetyo, Yudha Eka; Rahardi, Rustanto; Rahmadani, Desi (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
Mathematical problem-solving ability is essential in learning activities at school and real life. Until now, students' abilities in solving mathematical problems vary, especially in solving non-routine problems, such as jumping task problems. These differences can be influenced by several factors, one of which is the adversity quotient. This study determined the mathematical problem-solving ability according to Polya's stages to solve jumping task problems based on students' adversity quotient. This study was conducted by involving 22 students in one of the junior high schools (SMP) in Malang Regency as research subjects. In this study, the researcher acted as the main instrument assisted by the Adversity Response Profile (ARP) questionnaire, problem-solving question sheets, and semi-structured interview guidelines. This study began with the provision of a questionnaire. Continued by working on test questions and selecting three students to conduct interviews. This study found that climber students tend to be more able to solve problems according to Polya's stages tactically and effectively, and have better verbal skills. Students have also been able to understand the issues contained in the jumping task questions. However, all students tend to skip the stage of re-examining the process and answers.